An overview of the universal immunization programme in India: a multi-level discussion - M. Hasan Askari; Krishnendu Gupta (International Journal Of Community Medicine And Public Health, 2026)
Background: The World Health Organisation (WHO) first introduced the idea of an immunization programme in 1974 with the inauguration of the “Expanded Programme on Immunization” (EPI). In India, EPI was launched in 1978 and was renamed the universal immunization programme (UIP) in 1985. It is crucial to talk about the situation at the global and local levels to better understand the immunization programme’s implementation status. Methods: The primary objective of this paper is to illustrate the performance of the immunization programme in India, starting with India and going down to the district level, the study is viewed as a multi-level discussion. The study is based on secondary data gathered from various sources. Several maps and diagrams have been prepared to provide a broad overview of immunization programme’s performance for easier comprehension. Results: The study revealed regional differences in immunization programme performance across the whole country, including at the state, district and block levels. The discussion highlights that the declining IMR in India and West Bengal which reflects improvement in child healthcare, immunization, nutrition and related health services. India has achieved relatively favourable vaccination coverage compared with several other developing countries. The state of West Bengal has also demonstrated satisfactory immunization coverage over time. However, significant spatial disparities exist within the country, states and different districts. Conclusions: The study suggests that strengthening the immunisation programme requires a combination of better infrastructure, technology, community engagement and healthcare workforce support.